Investing to gain others’ trust: Cognitive abstraction increases prosocial behavior and trust received from others - van Houwelingen, Gijs; van Dijke, Marius (PLOS ONE, 2023)
Being trusted has many positive implications for one’s wellbeing (e.g., a better career, more satisfying interpersonal relationships). Scholars have suggested that people actively attempt to earn trust. However, it is not clear what makes people invest in actions that may earn them trust. We propose that cognitive abstraction (more than concreteness) facilitates seeing the long-term benefits of performing behaviors (i.e., prosocial behaviors) for gaining trust. We conducted a survey among employees and their supervisors and two yoked experiments—total N = 1098 or 549 pairs. In support of our claim, we find that cognitive abstraction leads to more prosocial behavior, which subsequently increases trust received. Furthermore, the effect of abstraction on the performance of prosocial behavior is limited to situations where such behavior can be observed by others (and thus be a basis for gaining observers’ trust). Our research shows when and why people decide to act in ways that may gain them trust and clarifies how cognitive abstraction influences the display of prosocial behavior and the subsequent trust received from fellow organization members.